Evidance based case report (EBCR) : intervensi terapi genggam jari dalam penurunan skala nyeri pada pasien post operasi laparotomi: Case report - Haura Syafa Rizqa; Rochmawati, Erna (Sahabat Publikasi Kuu, 2023)
Background: Laparatomy is a surgical procedure by opening the abdominal cavity through an incision. One of the nursing problems that often appears in post laparatomy patients is severe acute pain or acute pain that often occurs during the treatment or healing period in patients who have been treated laparotomy. Puspose: To know the intervention of finger-held therapy in the reduction of pain scale in postoperative laparotomy patients. Methods: This type of research is case study research. The focus in this study was the application of finger-held therapy to lower the pain scale in post op laparatomy patients. Results:There were 3 people who experienced a decrease in the pain scale from before the intervention was carried out by administering finger grip therapy. The results of the study showed that there was an effect of the pain scale before and after finger grip therapy in both post-laparotomy cases. Conclusion: Handheld finger therapy is able to reduce the scale of pain in laparatomy post op patients.